(untitled) (Journal of Human Sciences, 2021)
This study is considered a proposal to add a special course labeled (tQur’anic story) in the primary education stages in Libya, or to add a special section to the Quranic story in the syllabus (Islamic education) in the primary education stages, and not a field study; Because the application of this proposal requires at least two academic years for the researcher to prove the extent to which the tQur’anic story is used in developing thinking among children in primary education stages in Libya, as this study is considered an invitation to study the development of thinking in the light of the stories of the Noble Qur’an; Because the Quranic story is one of the topics that occupied a large space in the Holy Qur’an, as it contributes to what it presents to man from the summary of human experiences in removing the veil of negligence and forgetting, and refining the human memory and convincing him of what is correct. The most important feature of this study is that it clarifies the concept of the Quranic story, its elements, characteristics, and objectives, with an explanation of the concept of thinking and its connection with the Holy Qur’an by explaining the methods of mental education, and the rules for developing and advancing thinking in the Holy Qur’an, with a presentation of examples of the stories of the Holy Qur’an and how the teacher narrates them to students . The most important findings of the study are that the use of the analytical narration of the Quranic story, and the conclusions and implications it contains, and the selection of the appropriate method in which the story is told for each stage of education, has a significant impact on the development of thinking in children, as the most important thing recommended by the study is the necessity of Reconsidering the methods of teaching and learning the Noble Qur’an, and paying close attention to issues related to thinking, contemplation and contemplation of the Noble Qur’an, a great interest in education curricula in Libya.